Perlindungan Hukum bagi Pemegang Hak Cipta Karya Digital terhadap Praktik Plagiarisme di Media Sosial - Rikyi Zaenudin; Aturkian Laia (INDO PUBLISHING, 2026)
The development of social media has triggered massive dissemination of digital works while increasing the risk of plagiarism without the copyright owner's consent. This legal-doctrinal research aims to examine the status of digital works as protected objects, analyze their legal protection against social media plagiarism, and formulate available legal remedies. Utilizing statute and conceptual approaches, this study relies on the Copyright Act and the Electronic Information and Transactions (ITE) Act. The results indicate that digital works qualify for protection as long as they possess originality and tangible form. However, Indonesian regulations do not explicitly accommodate social media characteristics, making current protection general and reactive. Furthermore, the application of the notice-and-takedown principle for digital platforms remains uncomprehensively regulated. Copyright holders can pursue both non-litigation and litigation channels. This study recommends strengthening technical regulations regarding digital platforms' obligations and clarifying the definition of digital works within the national legal framework.